Unemployment assistance and transition to employment in Argentina - Ana Iturriza; Arjun S. Bedi; Robert Sparrow (Institute for the Study of Labor (IZA), 2008)
In 2001-02, Argentina experienced a wrenching economic crisis. Plan Jefes, implemented in May 2002, was Argentina's institutional response to the increase in unemployment and poverty triggered by the crisis. The program provided a social safety net and appears to have successfully protected some families against indigence. Despite this success, the continued existence of the program, which provides benefits to eligible unemployed individuals for an unlimited duration, may have unappealing long-term consequences. Reliance on the plan may reduce the incentive to search for work and in the long-run may damage individual employability and perpetuate poverty. Motivated by these concerns, this paper examines the effect of participating in Plan Jefes on the probability of exiting from unemployment. Regardless of the data set, the specification and the empirical approach, the evidence assembled in this paper shows that for the period under analysis individuals enrolled in the Plan are between 12 to 19 percentage points less likely to transit to employment as compared to individuals who applied but did not join the Plan. The negative effect of the program tends to be larger for females and as a consequence, over time, the program becomes increasingly feminized. Prima facie, the estimates suggest that programs such as Plan Jefes need to re-consider the balance between providing a social safety net and dulling job-search incentives.
urn:nbn:de:101:1-2008071146
Keywords: J64; 330; Unemployment assistance programs; unemployment transitions; Argentina; Arbeitslosenversicherung; Berufliche Integration; Arbeitsangebot; Ökonomischer Anreiz; Argentinien